Great kids' rooms decorating ideas for their years at home - Scheffler, Carol (New York Sterling Publishing, 2003)
"A photo-filled style guide offers ideas for imaginative themes for every stage of childhood. Practical instructions cover basic techniques for changing floors, walls, windows, lighting, and storage. Comes with tips on how to alter its look to express whichever approach rustic, sporty, wild, or playful-you and the kids choose"--Provided by publisher.
Keywords: Interior decoration; Children's rooms